Revisiting the law and governance of trafficking, forced labor and modern slavery - Kotiswaran, Prabha (Colección de libros electrónicos de ULoyola, 2017)
In the decades following the globalization of the world economy, trafficking, forced labor and modern slavery have emerged as significant global problems. States negotiated the Palermo Protocol in 2000 under which they agreed to criminalize trafficking, primarily understood as an issue of serious organized crime.